Safety Outcomes Following Spine and Cranial Neurosurgery: Evidence From the National Surgical Quality Improvement Program. Issue 4 (October 2018) - Rock, Andrew K.; Opalak, Charles F.; Workman, Kathryn G.; Broaddus, William C.
Abstract : Background: The American College of Surgeons National Surgical Quality Improvement Program (ACS-NSQIP) was used to establish predictors for 30-day postoperative complications following spine and cranial neurosurgery. Materials and Methods: The ACS-NSQIP participant use files were queried for neurosurgical cases between 2005 and 2015. Prevalence of postoperative complications following neurosurgery was determined. Nested multivariable logistic regression analysis was used to identify demographic, comorbidity, and perioperative characteristics associated with any complication and mortality for spine and cranial surgery. Results: There were 175, 313 neurosurgical cases (137, 029 spine, 38, 284 cranial) identified. A total of 23, 723 (13.5%) patients developed a complication and 2588 (1.5%) patients died. Compared with spine surgery, cranial surgery had higher likelihood of any complication (22.2% vs. 11.1%; P <0.001) and mortality (4.8% vs. 0.5%; P <0.001). In multivariable analysis, cranial surgery had 2.73 times higher likelihood for mortality compared with spine surgery (95% confidence interval, 2.46-3.03; P <0.001), but demonstrated lower odds of any complication (odds ratio, 0.93; 95% confidence interval, 0.90-0.97; P <0.001). There were 6 predictors (race, tobacco use, dyspnea, chronic obstructive pulmonary disease, chronic heart failure, and wound classification) significantly associated with any complication, but not mortality. Paradoxically, tobacco use had an unexplained protective effect on at least one complication or any complication. Similarly, increasing body mass index was protective for any complication and mortality, which suggests there may be a newly observed "obesity paradox" in neurosurgery. Conclusions: After controlling for demographic characteristics, preoperative comorbidities, and perioperative factors, cranial surgery had higher risk for mortality compared with spine surgery despite lower risk for other complications. These findings highlight a discrepancy in the risk for postoperative complications following neurosurgical procedures that requires emphasis within quality improvement initiatives.